Service at UiTM residential hostel cafeterias - is it satisfactory? - Abd Ghani, Fatimah; Mohd Zahari, Mohd Salehuddin; Ramli, Noorazlin; Jusoff, Kamaruzaman; Md. Zaini, Zetty Madina; Hamid, Munirah; Samsudin, Azlina; Ngali, Norzaidah; Rahmat, Norazlina (IDOSI Publications, 2011)
Students are sandwiched between the intensity of time to be devoted to their studies and to pursue their nutritional requirements. Hence, they are pressured to patronize the university’s food service as an alternative source to for food and beverages. This study empirically examines students’ acceptance level and satisfaction on the service delivery attributes at Universiti Teknologi MARA (UiTM) hostel cafeterias. Through self-reported experiences on three dimensions of service delivery attributes, students who reside in UiTM Shah Alam hostels, namely Kolej Seroja, Kolej Anggerik and Kolej Perindu went through a questionnaire survey. Results revealed that food and beverages and service attributes are the major determinants looked at by students when dining at UiTM hostel cafeterias and they had the same expectations as other restaurant customers. They expect decent food and beverages with an acceptable degree of service. Nevertheless, their expectations were not met. In conclusion, UiTM as an educational institution should have more systematic procedures in combating the above mentioned issues for the benefit of students as stakeholders and at the same time boost confidence among parents or guardians. Therefore, the students’ expressions on these attributes have directly given significant impact not only to them but also to the operators as well as UiTM as a whole.